2005
DOI: 10.1002/ejic.200500498
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Soluble Arene Ruthenium Complexes Containing a trans‐1,2‐Diaminocyclohexane Ligand as Enantioselective Transfer Hydrogenation Catalysts in Aqueous Solution

Abstract: The cationic chloro complexes [(arene)Ru(H2N∩NH2)Cl]+ (1: arene = C6H6; 2: arene = p‐MeC6H4iPr; 3: arene = C6Me6) have been synthesised from the corresponding arene ruthenium dichloride dimers and enantiopure (R,R or S,S) trans‐1,2‐diaminocyclohexane (H2N∩NH2) and isolated as the chloride salts. The compounds are all water‐soluble and, in the case of the hexamethylbenzene derivative 3, the aqua complex formed upon hydrolysis [(C6Me6)Ru(H2N∩NH2)OH2]2+ (4) could be isolated as the tetrafluoroborate salt. The mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 56 publications
2
66
0
Order By: Relevance
“…The spectroscopic (MS, In contrast to arene ruthenium chloro complexes containing chelating N,N-ligands, which hydrolyze in water to give the corresponding cationic aqua complexes [11,12,39] The para-cymene chloro complex 5 crystallizes in the monoclinic centrosymmetric space group P2 1 /n. The asymmetric unit comprises only one molecule, the molecular structure of which is depicted in Fig.…”
Section: Synthesis Of the Chloro Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The spectroscopic (MS, In contrast to arene ruthenium chloro complexes containing chelating N,N-ligands, which hydrolyze in water to give the corresponding cationic aqua complexes [11,12,39] The para-cymene chloro complex 5 crystallizes in the monoclinic centrosymmetric space group P2 1 /n. The asymmetric unit comprises only one molecule, the molecular structure of which is depicted in Fig.…”
Section: Synthesis Of the Chloro Complexesmentioning
confidence: 99%
“…A new impetus came into this field in 1988, when Ludi, Merbach, Bürgi and co-workers showed that arene ruthenium aqua complexes previously observed by NMR spectroscopy [2] can be isolated under certain conditions; the characterization of the cation [(g 6 -C 6 H 6 )Ru(H 2 O) 3 ] 2+ by singlecrystal X-ray structure analysis of the sulfate salt can be considered as a breakthrough [6]. In the 1990s we found that the chloride or tetrafluoroborate salts of cationic arene ruthenium complexes are well soluble in water, the arene ruthenium bond being robust toward hydrolysis [7][8][9], which resulted in a rapid development of arene ruthenium chemistry in aqueous solution [10], especially as far as water-soluble catalysts for transfer hydrogenation reactions in aqueous solution are concerned [11][12][13][14][15][16][17][18][19][20][21]. The hydrogenation of carbon dioxide to give formic acid in aqueous solution is an attractive approach to the use of carbon dioxide as an economical and ecological C 1 source [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The transition-metal-based enantioselective hydrogenation or transfer hydrogenation of ketones in organic solvents [2][3][4][5][6][7][8][9][10] as well as in aqueous solutions [11][12][13][14][15][16][17][18][19][20][21] is one of the most commonly used synthetic approaches. Biotransformations of organic substrates by various enzymes have also found widespread applications, particularly because of their capability to efficiently perform enantioselective transformations.…”
Section: Introductionmentioning
confidence: 99%
“…(1)]. [7][8][9][10][11] In attempts to prepare helical dinuclear ruthenium(II) benzene complexes as a part of our on-going project on helical metal complexes, [12][13][14][15] we reacted [Ru-A C H T U N G T R E N N U N G (C 6 H 6 )Cl 2 ] 2 with the helical tetradentate N-donor ligands RL (R is H or Me). The X-ray crystal structure of the ligand HL has been reported earlier by us.…”
Section: Resultsmentioning
confidence: 99%